A cluster of Shiga Toxin-producing Escherichia coli O157:H7 highlights raw pet food as an emerging potential source of infection in humans. (6th May 2021) - Kaindama, Lukeki; Jenkins, Claire; Aird, Heather; Jorgensen, Frieda; Stoker, Kelly; Byrne, Lisa
Abstract: In August 2017, a cluster of four persons infected with genetically related strains of Shiga toxin-producing Escherichia coli (STEC) O157:H7 was identified. These strains possessed the Shiga toxin ( stx ) subtype stx2a, a toxin type known to be associated with severe clinical outcome. One person died after developing haemolytic uraemic syndrome. Interviews with cases revealed that three of the cases had been exposed to dogs fed on a raw meat-based diet (RMBD), specifically tripe. In two cases, the tripe had been purchased from the same supplier. Sampling and microbiological screening of raw pet food was undertaken and indicated the presence of STEC in the products. STEC was isolated from one sample of raw tripe but was different from the strain causing illness in humans. Nevertheless, the detection of STEC in the tripe provided evidence that raw pet food was a potential source of human STEC infection during this outbreak. This adds to the evidence of raw pet food as a risk factor for zoonotic transmission of gastrointestinal pathogens, which is widely accepted for Salmonella, Listeria and Campylobacter spp. Feeding RMBD to companion animals has recently increased in popularity due to the belief that they provide health benefits to animals. Although still rare, an increase in STEC cases reporting exposure to RMBDs was detected in 2017. There has also been an increased frequency of raw pet food incidents in 2017, suggesting an increasing trend in potential risk to humans from raw pet food. Recommendations to reduce the risk of infection included improved awareness of risk and promotion of good hygiene practices among the public when handling raw pet food.